Avian Expression Patterns and Genomic Mapping Implicate Leptin in Digestion and TNF in Immunity, Suggesting That Their Interacting Adipokine Role Has Been Acquired Only in Mammals - Seroussi, Eyal; Knytl, Martin; Pitel, Frédérique; Elleder, Daniel; Krylov, Vladimir; Leroux, Sophie; Morisson, Mireille; Yosefi, Sara; Miyara, Shoval; Ganesan, Saibaba; Ruzal, Mark; Andersson, Leif; et al. (International journal of molecular sciences, 2019)
In mammals, leptin and tumor-necrosis factor (TNF) are prominent interacting adipokines mediating appetite control and insulin sensitivity. While TNF pleiotropically functions in immune defense and cell survival, leptin is largely confined to signaling energy stores in adipocytes. Knowledge about the function of avian leptin and TNF is limited and they are absent or lowly expressed in adipose, respectively. Employing radiation-hybrid mapping and FISH-TSA, we mapped TNF and its syntenic genes to chicken chromosome 16 within the major histocompatibility complex (MHC) region. This mapping position suggests that avian TNF has a role in regulating immune response. To test its possible interaction with leptin within the immune system and beyond, we compared the transcription patterns of TNF, leptin and their cognate receptors obtained by meta-analysis of GenBank RNA-seq data. While expression of leptin and its receptor (LEPR) were detected in the brain and digestive tract, TNF and its receptor mRNAs were primarily found in viral-infected and LPS-treated leukocytes. We confirmed leptin expression in the duodenum by immunohistochemistry staining. Altogether, we suggest that whereas leptin and TNF interact as adipokines in mammals, in birds, they have distinct roles. Thus, the interaction between leptin and TNF may be unique to mammals.
Keywords: kur domácí; Gene Expression Regulation; leptin; mapování pomocí radiačních hybridů; RNA, Messenger; Receptors, Tumor Necrosis Factor; Cell Line; Chromosome Mapping; Digestion; Leptin; Mammals; Tumor Necrosis Factor-alpha; Metaphase; Chickens; Receptors, Leptin; signální transdukce; TNF; syntenie; immune system; leptinové receptory; Radiation Hybrid Mapping; Signal Transduction; radiation-hybrid mapping; Synteny; savci; Animals; ženské pohlaví; mapování chromozomů; FISH-TSA; Duodenum; zvířata; regulace genové exprese; receptory TNF; digestive tract; buněčné linie; metafáze; TNF-alfa; Female; messenger RNA; trávení; duodenum; chicken